(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Pre-operative prediction of difficulties which may occur during laparoscopic cholecystectomy can help in reduction of operative and postoperative complications. Objectives:To study the value of preoperative ultrasound findings for predicting difficulties encountered during laparoscopic cholecystectomy and to assess the usefulness of these findings to identify patients at high risk of conversion from laparoscopic to open cholecystectomy. Methods: A prospective study of 200 patients who underwent laparoscopic cholecystectomy for symptomatic cholelithiasis. Pre-operative abdominal ultrasound was done. The diagnosis of gall stones was made and the presence of ancillary findings was recorded. Five ancillary ultrasound findings were assessed. These included; thickened gall bladder wall more than 4mm, presence of pericholecystic fluid, severely contracted gall bladder, empyma, and gall bladder filled with stones. Ultrasound findings were compared with the operative findings. Results:In 36 patients who had one or more of these findings laparoscopic Cholecystectomy was difficult in 22(61.1%) of them. Thick wall gall bladder > 4mm has the highest sensitivity (69%) and the presence of pericholecystic fluid has the highest specificity (100%) in predicting difficult laparoscopic cholecystectomy and the presence of more than 2 ancillary findings yielded an accuracy rate of (100%). Conversion to open cholecystectomy was needed in 13.9% of these patients. The rates of difficult laparoscopic cholecystectomy and conversion to laparotomy were much lower in those patients who had no ancillary findings (4.3%) and (1.2%) respectively. Conclusion:Preoperative ultrasound findings are of value for predicting difficulties encountered during laparoscopic cholecystectomy which may require conversion to open cholecystectomy. Keywords: Laparoscopic surgery, Cholecystectomy, Ancillary ultrasound findings.